Information and Communication Technology as Predictor for Quality Instructional Delivery Approach among Pre-Service Teachers - Balqis Olabisi Popoola; Hameed Olalekan Bolaji (Indonesian Journal of Multidiciplinary Research, 2023)
This study investigated Information and Communication Technologies (ICTs) as predictors for quality instructional delivery among teaching practice undergraduates in Oyo state. A descriptive survey research design was used for the study and the population was 1286 teaching practice undergraduates at Kola Daisi University. The sample size of 291 was determined using Krejcie and Morgan sampling table. A five-point rating scale questionnaire validated by experts was used for data collection. The measurement of the internal consistency method was used to establish the reliability of the instrument and the application of Cronbach Alpha yielded reliability coefficients of 0.97 and 0.87 for the two sections and overall reliability of 0.90. Frequency tables and Pearson product-moment correlation were used to answer research questions. ICT usage among teaching practice undergraduates is high; the level of quality instructional delivery among teaching practice students is high while there was a significant relationship between the two variables. Based on the findings, teaching practice students and polytechnic lecturers should be more equipped with ICT facilities to aid more in their teaching experiences. It was, therefore, recommended that management and various stakeholders should be sensitized to provide schools with the required infrastructural ICT facilities to enhance effective educational service delivery through quality teaching and learning.